(untitled) (Iranian Journal of Kidney Diseases, 2010)
Renal insufficiency occurs in a considerable proportion of patients with sickle cell disease. Common advanced glomerular lesions include focal segmental glomerulosclerosis and nonimmune membranoproliferative glomerulonephritis. Due to the paucity of data supporting an immune-mediated pathophysiology, anti-inflammatory and immunosuppressive therapies have not been successfully evaluated in such patients. We present a case of membranoproliferative glomerulonephritis in a postpartum patient with sickle cell disease, where treatment with steroids was helpful.